Readiness of Village Human Resources in Implementing The Red and White Cooperative - Rahmi, R; Azhari, A.; Jamaludin, J (International Journal of Accounting and Economics Studies, 2025)
This study aims to evaluate the readiness of village human resources for the successful implementation of the Red and White Cooperative in rural Indonesia. The research focuses on identifying key factors that influence the readiness of villagers to engage with and manage cooperative programs, including education, awareness, managerial skills, and institutional support. Using a qualitative research design, this study employs a literature review approach to analyze existing scholarly articles and reports. Data was analyzed using thematic coding to identify recurring themes and key patterns relevant to the research objectives. The findings reveal that while there is significant interest in participating in the cooperative, many villagers face challenges due to limited education, lack of formal training, and insufficient awareness of modern cooperative models. Furthermore, managerial skills are often informal and inadequate for managing complex cooperatives, and institutional support is sporadic. Cultural resistance to formal cooperative structures also poses a challenge. These results contribute to the literature on rural development and cooperative management, providing new insights into the specific barriers to successful cooperative implementation in rural settings. This research offers valuable contributions to both academic knowledge and practical strategies for improving cooperative success in rural areas. Policymakers can use the findings to design more targeted educational and institutional support programs. Future research should focus on primary data collection to explore these themes further, particularly in remote rural areas, and investigate the role of digital technologies in overcoming some of the identified barriers.